P-211 A blue light partnership: innovative collaboration between an ambulance service and hospice. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Murphy-Jones, Georgina; Daniels, Charles; Catley, Karina; Laverty, Diane; Phillips, Caroline; Tipping, Inderia
Abstract : Background: A Metropolitan Ambulance Service has partnered with Macmillan Cancer Support on a two year programme to improve end-of-life care. This aims to reduce inappropriate hospital conveyance and increase staff knowledge and confidence; when surveyed 50% of ambulance clinicians 'agreed' or 'strongly agreed' with feeling confident in their skills and knowledge of end-of-life care. Aims: Evaluate the impact of a co-production programme on ambulance clinicians' knowledge and confidence in responding to patients in the last phase of life. Inform development of the Ambulance Service's end-of-life care strategy. Methods: An interested hospice was invited to co-design and co-deliver an interactive CPD event for ambulance clinicians. Paramedic End-of-Life Care Champions were supported by the ambulance service Macmillan team, Hospice Consultant and hospice telephone helpline nurse manager. The event was evaluated via online survey and staff interviews captured learning which may facilitate spread of hospice co-production service wide. Results: Results evidence the programme's success: 34 operational ambulance staff attended; 100% agreed or strongly agreed that it positively influenced their practice: Increased confidence in skills and knowledge of end–of–life care, 78% respondents agreed/strongly agreed with feeling confident. 47% reported learning about hospice services which they could use in practice; Case based discussions were unanimously regarded as an excellent method of learning, with palliative care expertise valued; Hospice staff unexpectedly learnt important lessons from ambulance colleagues which will improve their service. Conclusions: Alongside learning for ambulance clinicians there was unintended but beneficial learning for hospice staff. The hospice and Macmillan teams provided essential support to the Paramedic End-of-Life Care Champions but the production of a 'How to run an Interactive end-of-life care training event' kit would reduce the need for central support. The benefits to hospices in utilisation of, and improvement in their services and their staff may help encourage wider support from hospices to be involved in similar co-production events.